KEMAUAN MEMBAYAR (WILLINGNESS TO PAY) CALON PENUMPANG TERHADAP RENCANA PELAYANAN TRANSJOGJA RUTE YOGYAKARTA-KALIURANG - Hidayat, Aditya Mahatidanar; Kushari, Berlian (Teknisia, 2015)
TransJogja is a public bus system that serves Yogyakarta city and its vicinity using mid-sized air conditioned buses. The system, that was introduced in February 2008, currently runs daily from 05.30 to 21.30 on it 4 trunk routes. Recently, a plan of opening some feeder routes has been considered to expand its service coverage so as to include potential trip generator regions, including areas along Yogyakarta – Kaliurang road. The purpose of this study was twofold, i.e. to investigate prospective passengers’ willingness to pay (WTP) TransJogja service planned to run Yogyakarta – Kaliurang route and to study which factors that likely determine the formation of passengers’ WTP. Stated preference technique was used to collect prospective passengers’ opinion on the price that they would pay provided certain service characteristics. In a view that one’s WTP may also be influenced by his/her own socioeconomic background in addition to the service features offered, respondents’ socioeconomic information such as age, gender, income level, etc. were also collected and used to study their influence to the stated price to pay. Based on 655 observations, a majority of 26,1% respondents stated 3.000 rupiahs as the price they would pay for Yogyakarta-Kaliurang TransJogja services, while another 23,97% stated 2.000 rupiahs. These prices correspond to various combinations of service features, including varied seating capacity, inclusion or exclusion of air conditioning system (AC), bus stops, varied peak and off-peak headway, varied service hours, and application of special rates for students. Further study using multiple linear regression method indicated that respondents’ socioeconomic features that include one’s gender, age, place of stay (along Kaliurang Rd or otherwise), and monthly transportation-related expenditure had a greater share in determining his/her WTP, rather than service features that include seating capacity, AC, and student’s special rate. Therefore, it was recommended that the concerned office should take consumers’ socioeconomic factors into consideration in their future decision on passenger tariff should the Yogyakarta-Kaliurang route of TransJogja services is to open.